TANGGUNG JAWAB NOTARIS TERKAIT PEMBATALAN AKTA YANG DIAKIBATKAN OLEH KELALAIAN DALAM MENJALANKAN JABATANNYA (CONTOH KASUS PUTUSAN NOMOR: 73/PDT/2018/PT.DKI) - William Hendarsin; Gunawan Djajaputra (Faculty of Law - Tarumanagara University, 2020)
Public Notary is an official authorized to make an authentic deed. An authentic deed has perfect proof of strength because in its making was carried out by an authorized official and attended by witnesses, but an authentic deed made by a Public Notary can be a deed under the hand in this case the strength of proof is not perfect if the making of an authentic deed has been proven to violate the provisions of the act Law Number 2 of 2014 concerning Amendment to Law number 30 of 2004 concerning Position of Notary Public. In making an authentic deed, the Notary is required to make a deed based on the agreement of the parties, but in practice often the Notary violates this and makes a deed that is only approved by one party. As is the case in Decree Number 73/PDT/2018/PT.DKI, that in making binding purchase agreements for land and buildings based on accounts receivable debts, of course, violates regulatios and causes losses fot Debtors (Plaintiffs) who sue Creditors and Notary who make this agreement. So the Plaintiff filed a lawsuit in court so that the sale and purchase deed made under the sale and purchase agreement is null and void.